Immunohistochemical study of correlation between histologic changes and radiologic features in pericoronal tissues of impacted wisdom teeth - Sayed Mohammad Razavi; Sara Siadat; Mozhdeh Mehdizadeh; Bijan Movahedian; Daryoush Hasheminia (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Third molars have the greatest incidence of impaction. There is no general agreement on the removal of asymptomatic impacted third molars. EGFR might be an indicator of increased potential for tumoral and cystic changes. The aim of this study was to investigate the expression of EGFR marker in the follicles of impacted wisdom teeth and its relation to radiologic features.Materials and methods: In this cross-sectional/analytical research, 40 samples of wisdom tooth follicles, embedded in paraffin blocks, were studied. After preparing the specimens and primary observation of H&E slides, immunohistochemical technique was used for expression of EGFR marker. EGFR staining pattern (membrane only, cytoplasm only or combined cytoplasm and membrane staining) was evaluated in the odontogenic epithelium of follicles. Data were analyzed with Mann-Whitney and logistic regression tests using the SPSS software (α=0.05). Results: Expression of EGFR marker with membrane-only staining pattern in follicles with radiolucencies >2.5 mm was significantly higher than follicles with radiolucencies <2.5 mm. (p value < 0.001). However, no significant differences were detected between the two groups in cytoplasm-only pattern (p value = 0.13) and combined cytoplasmic and membrane pattern (p value = 0.13). Discussion: The number and intensity of stained cells in membrane-only pattern were higher in follicles with radiolucencies >2.5 mm compared to follicles with radiolucencies <2.5 mm, indicating faster cell proliferation. Therefore, it is suggested that third molars with radiolucencies >2.5 mm be removed as soon as possible. However, the absence of abnormal radiolucency does not indicate healthy follicles without pathologic changes.Key words: Human EGFR protein, Immunohistochemistry, Impacted tooth.